Reconsideration on the value of biomaterials in the treatment of anal fistulas - Cao Jiawei; Lu Meijuan; Su Dan; Xiang Xiaoqiang; Zhu Peixuan; Ren Donglin (结直肠肛门外科)
The implantation of biomaterials to fill fistula tracts is a significant method for preserving the sphincter during anal fistula surgery. Procedures such as anal fistula plug implantation and BioLIFT have shown good results over the past 20 years. However, recent clinical outcomes have been less satisfactory, with a cure rate of less than 50% and high economic costs, leading many guidelines to not recommend biomaterial implantation as a first-line treatment for anal fistulas. Given the demand for sphincter-preserving techniques in various scenarios, surgeons are re-evaluating the scientific basis of using biomaterials to promote fistula healing. Is there an inherent superiority in the materials themselves? Are the variations in cure rates related to differences in indications, surgical techniques, postoperative care, and other factors? This paper systematically reviews and analyzes these issues.